What Europe Day can mean for ASEAN - Webb, Graham Gerard-Ong (2016)
THE late Irish writer Oscar Wilde once observed," Most modern calendars mar the sweet simplicity of our lives by reminding us that each day that passes is the anniversary of some perfectly uninteresting event."